Back Cover: ZnO Nanostructures for Dye‐Sensitized Solar Cells Using the TEMPO+/TEMPO Redox Mediator and Ruthenium(II) Photosensitizers with 1, 2, 3‐Triazole‐Derived Ligands (ChemPlusChem 12/2016). Issue 12 (10th November 2016) - Wahyuono, Ruri Agung; Schulze, Benjamin; Rusu, Mihai; Wächtler, Maria; Dellith, Jan; Seyring, Martin; Rettenmayr, Markus; Plentz, Jonathan; Ignaszak, Anna; Schubert, Ulrich S.; Dietzek, Benjamin
Abstract : The cover picture shows a ZnO nanoflower with Ru II complex bearing a 1, 2, 3‐triazole‐derived N C N cyclometalated ligand. Toward dye‐sensitized solar cells (DSSCs) free from iodine and thiocyanate, TEMPO+/TEMPO electrolyte in combination with Ru II complexes bearing 1, 2, 3‐triazole‐derived N N N‐, N C N‐, and C N C‐coordinating ligands show promising power conversion and external quantum efficiencies in ZnO‐based DSSCs. Details are given in the Full Paper by B. Dietzek et al. onpage 1281 in Issue 12, 2016 (DOI: 10.1002/cplu.201600377).